Morphology and taxonomy of Southern Australian genera of Crouanieae schmitz (Ceramiaceae, Rhodophyta). - Wollaston, Elise M. (Australia CSIRO Pub., 1968)
Australian Journal Botany 16:217-417
Keywords: Red algae; Ceramiaceae